The Development of an Integrated Smart Agrivoltaic System for Real-Time Monitoring and Automated Control in Spinach and Mustard Green Cultivation: A Case Study in Salatiga, Indonesia - Santika, Maria; Hernanda, Otniel; Reformasi, Fransiskus; Wisesa, Amadeo (Lembaga Pengembangan Kinerja Dosen, 2025)
This research develops an agrivoltaic farming system to improve land use by combining solar energy generation with agricultural practices. This system uses solar panels to provide green energy and also protects plants from extreme heat, reduces water evaporation and increases crop yields. Design of monitoring and control tools using Arduino Mega integrating soil moisture, temperature and water pH sensors to ensure optimal agricultural conditions. The results of this research show that the solar panel configuration produces an average voltage of 49.68 V and the monitoring system displays data effectively, and the soil moisture control system achieves an error rate of 2.24% for spinach plants and 2.60% for green mustard plants. Additionally, an error rate of 0.38% was recorded for temperature measurements.